The binding of haloperidol to human blood platelets and interactions with 5-hydroxytryptamine and dopamine. - Boullin, D J (1978)
1 The binding of [3H]-5-hydroxytryptamine ([3H]-5-HT), [3H]-haloperidol and [3H]-dopamine to human blood platelets was investigated and the effects of unlabelled haloperidol on [3H]-5-HT binding and (+)- and (-)-butaclamol on [3H]-haloperidol were studied. 2 Scatchard analysis did not show any specific binding of [3H]-haloperidol or [3H]-dopamine to platelets, but two binding sites were identified for binding of [3H]-5-HT. 3 Unlabelled haloperidol reduced the binding of 5-HT in concentrations comparable to those inhibigint 5-HT-induced platelet aggregation; (+)- and (-)-butaclamol did not affect the binding of [3H]-haloperidol. 4 It is concluded that haloperidol binding represents saturation of the platelet membrane, and that the platelet is not a suitable model for investigation of dopamine-drug interactions.